2018
DOI: 10.3382/ps/pey176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic (Bacillus subtilis) supplementation on meat quality characteristics of breast muscle from broilers exposed to chronic heat stress

Abstract: The aim of this study was to determine the impact of probiotic feeding and chronic heat stress on meat quality, total lipid and phospholipid contents, lipid oxidation, antioxidant capacity, and heat shock protein abundance of broiler breast muscle. A total of 240 male broilers (5 birds per pen) were subjected to 4 treatments consisting of a 2 × 2 factorial design. Broilers were kept at 21-32-21°C for 10 h daily (heat stress, HS) or 21°C (thermoneutral condition) and fed a regular diet or the diet mixed with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 43 publications
5
41
3
2
Order By: Relevance
“…Therefore, the antioxidant capacity of muscle is also crucial to meat quality ( Pan et al., 2018 ). Previous studies indicated that heat stress had detrimental effects on muscle antioxidant status and increased MDA content ( Cramer et al., 2018 ; Wen et al., 2020 ). Similarly, in this study, we observed that heat stress increased muscle MDA content and decreased SOD and GSH-Px activity, which indicated a decreased muscle antioxidant capacity, alone with increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the antioxidant capacity of muscle is also crucial to meat quality ( Pan et al., 2018 ). Previous studies indicated that heat stress had detrimental effects on muscle antioxidant status and increased MDA content ( Cramer et al., 2018 ; Wen et al., 2020 ). Similarly, in this study, we observed that heat stress increased muscle MDA content and decreased SOD and GSH-Px activity, which indicated a decreased muscle antioxidant capacity, alone with increased lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, heat stress induced poor meat quality by lowering pH 24h and increasing cooking loss. Dietary supplementation with probiotics ( Cramer et al., 2018 ), prebiotics ( Tavaniello et al., 2020 ), and ginger ( Wen et al., 2020 ) were proved as effective additives to alleviate the negative effects of heat stress on meat quality of broilers. Chitosan oligosaccharides also reported as a promising feed additive to alleviate heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some previous studies found the beneficial impacts of probiotic feeding on broiler meat quality, such as WHC, oxidation stability, and tenderness (Aksu et al, 2005;Ali, 2010;Bai et al, 2016Bai et al, , 2017Kim et al, 2017;Zhou et al, 2010). Our recent research also revealed that probiotic feeding could alleviate oxidative damage of breast muscle of chickens that were previously exposed to cyclic heat stress (Cramer et al, 2016). As a few studies also postulated that the efficacy of probiotic feeding on meat quality attributes could be affected by dosage-level (Aksu et al, 2005;Ali, 2010;Bai et al, 2016Bai et al, , 2017Zhou et al, 2010), it would be reasonable to hypothesize that the beneficial impact of probiotic feeding on meat quality of heat-stressed broilers would be proportional to the amount of probiotic dosage level.…”
mentioning
confidence: 77%
“…This study is the first attempt to provide data on the effect of different levels of postbiotic RI11 on antioxidant activities in heat-stressed broilers. However, probiotics have been reported for their ROS removal capacity and promoting broiler health under normal [57] and high-temperature conditions [69].…”
Section: Acute Phase Proteins and Hsp70 Mrna Expressionmentioning
confidence: 99%